Negotiating Humanity through Innocence and Experience in William Blake’s Poetry - Nia Kurniawati; Kuswara; Dewi Sukmarawati (Journal of English Language Learning, 2026)
Abstract: This study explores how William Blake represents humanity through the concepts of innocence and experience in Songs of Innocence and Songs of Experience. Using a qualitative interpretive approach, the study analyzes selected paired poems to examine how moral awareness, emotional development, and humanitarian concerns are constructed through poetic contrast. The analysis is conducted through close reading and intertextual comparison, focusing on imagery, tone, and symbolic opposition between innocence and experience. The findings show that Blake does not present innocence and experience as opposing states, but as interconnected stages of human consciousness. Innocence is associated with trust, emotional openness, and moral hope, while experience reveals suffering, social injustice, and ethical failure. Through this tension, Blake invites readers to reflect on moral responsibility, empathy, and the impact of authority and social institutions on human life. The study argues that Blake’s poetic vision highlights humanity as a process shaped by moral struggle rather than fixed moral certainty. By combining textual analysis with a humanistic and reader-oriented perspective, this research contributes to literary studies by showing how Blake’s poetry continues to offer ethical insight into the human condition.